Selmecbánya helyi és regionális szerepe a magyar gazdaságban a 19-20. században - Koudela, Pál (Közép-Európai Közlemények, 2013)
The mining cities in the upper part of Hungary had leading economic role for centuries in the middle ages, and Selmecbánya was the most important of them. Selmecbánya was also the third biggist town in Hungary and one of the leading silver producer of the world in the 17.th and 18.th centuries. At the end of the 18.th century the mines run out of the silver and the economic relevance of these towns began to decrease. We show in this essay that decreasing economic situation doesn’t cause necesseraly mental disappointment and losing social values. The Kachelmann family started a succesful enterprise in steel industry at the beginning of the 19.th century and became a prominent member of Selmecbánya. Their activity helped the city to survive these hard times and showed positive example for other enterpreneurs and citizens in the whole region despite they found themselves in a very difficult administrative situation inherited from the 18.th century austrian patrimonial leading. To serve the mines were royal privileges and were hard to get them especially in this economic situation when producing steel were less and less profitable.